CHALLENGES OF ISLAMIC BANK MERGER IN INDONESIA: BOCR APPROACH - Rizal Rizal; Nil Firdaus; Wan Nor Aisyah Wan Yussof (IAIN Batusangkar, 2021)
This study aims to determine the opportunities and challenges with the merger of 3 BUMN Sharia Banks into Indonesian Sharia Banks (BSI). This study uses the BOCR (Benefit, Opportunity, Cost, and Risk) approach, part of the Analytical Network Process (ANP) approach. Through this approach, the priority value for each aspect (BOCR) will be obtained. The results of the study show that the Cost aspect has a priority value of 0.261. The benefits aspect (0.257), the risk aspect (0.244), and the lowest priority is the Opportunity aspect with a value of (0.236). Meanwhile, the priority strategy for the merger of these 3 BUMN Islamic Banks is professional Human Resources (HR).